The Euphorbiaceae (Spurge Family) in Bogor Botanic Gardens, Indonesia: Diversity, conservation and utilization (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Munawaroh E, Yuzammi, Purwanto Y. 2020. The Euphorbiaceae (Spurge Family) in Bogor Botanic Gardens, Indonesia: Diversity, conservation and utilization. Biodiversitas 21: 5021-5031. Euphorbiaceae (Spurge family) is the fourth largest family world-wide, consists of 1,354 species and 91 genera. The family is also a part of the Bogor Botanic Gardens collections. The Gardens has evolved to fulfill its mission through five principal functions: conservation, research, education, tourism, and environmental services. The aims of this study are to reveal the diversity, conservation, and its potential in the Bogor Botanic Gardens. This research was based on direct observation of all members of Euphorbiaceae family in the Gardens, as well as Registration Unit and the Garden’s catalog which were observed for more than 10 years. The Gardens collected 39 genera, 71 species, and 136 specimens where 91 specimens are trees, 38 specimens are shrubs, three specimens are climbers and four specimens are succulents. Most of the collections are native to Indonesia 75.91% (103 specimens) and only 33 specimens (24.09%) from overseas. Amongst native collections have dominated from Jawa 25.54% (34 specimens), Sumatra 24.08% (33 specimens). The others are from Sulawesi 9.48% (13 specimens), Kalimantan 7.29% (10 specimens), Maluku 6.56% (9 specimens), Papua 2.28% (three specimens), and Nusa Tenggara Timur 0.72% (one specimen). Many species of the family have potentially developed as traditional medicinal plants (11 species), ornamental plants (16 species), spices and vegetable (two species), timbers (14 species), rubber plants (one species), source of energy (two species) and toxic (six species). Several old collections have retained at the Gardens that aged over 75 years, such as Mallotus philippensis (Lam.) Mull. Arg. forma mollis, Acalypha wilkesiana Mull. Arg., Acalypha hispida Burm. var. sanderi (N.E.Br.) J. J. Sm., Acalypha wilkesiana Mull. Arg. forma Montana, Sapium aucuparium Jacq. and Ricinodendron heudelotii (Bail.) Heckel. A map of planting point of the Euphorbiaceae collections is provided.
Keywords: Bogor Botanic Gardens, conservation, diversity, Euphorbiaceae, potential